HUMAN RIGHTS AND ACCESS TO HEALTHCARE FOR PERSONS WITH ALBINISM IN AFRICA (African Disability Rights Yearbook, 2021)
Discrimination and stigma relating to persons with albinism remain the norm in many African countries. There are documented reports of how persons with albinism have been subjected to gross human-rights violations owing to their colour. While attention has been given to the killings of persons with albinism worldwide, little attention has been given to other human-rights violations they encounter while seeking social services, particularly healthcare services. Discrimination against persons with albinism can lead to deleterious health consequences and at the same time hinder access to care for them. Women are generally historically disadvantaged and continue to encounter challenges with regard to their sexual and reproductive health. Being a woman with albinism can aggravate the situation as these women may encounter multiple forms of discrimination in healthcare settings. Thus, this paper examines the human-rights challenges relating to the health of persons with albinism with a focus on women with albinism in Africa. It draws on the intersectionality approach to argue that women with albinism suffer from multiple forms of discrimination, which further compound access to healthcare services for them. It discusses the relevance of regional human-rights instruments in addressing the right to healthcare of women with albinism. In particular, the paper discusses the potential of the Protocol to the African Charter on Human and Peoples’ Rights on the Rights of Women in Africa and the norms developed by the African Commission on Human and Peoples’ Rights as well as its counterparts at the international level in advancing the right to health of women with albinism in the region. Furthermore, the paper recommends to the African Commission and African governments measures and steps to adopt in order to safeguard the right to health of women with albinism in the region.
Keywords: albinism; discrimination; stigma; human-rights violations; healthcare services; women; African Charter on Human and Peoples’ Rights; African Commission